Impact of global financial crunch on financially innovative microfinance institutions in South Asia - Faisal Mustafa; Ambreen Khursheed; Maham Fatima (Financial Innovation, 2018)
The wave of global financial crises (2008-2009) caused a surge in the capital flows of developed countries particularly, between developed and developing countries. The crunch hit all financial sectors with unanticipated severity. The study evaluates the role of a country's political practices in moderating the impact of global financial crunch on microfinance performance. Using the fixed effect panel regression method on the dataset comprising of 95 MFIs operating in South Asia from 2003 to 2012, we determine that microfinance operational capability shares a positive relationship with the institutional attributes of a country and our output reveals that impact of country's political practices is pervasive on the financial output of MFIs, liable to different levels of implementation. The findings further reveals that MFIs situated in countries having vigorous political practices are less severely affected by the economic crunch.
Keywords: F6; F65; G21; 650; Global financial crunch; South Asia; Microfinance institutions